Climate change and its impact on coastal cities: A case study from Alexandria - Ismail, Hend (AUC Knowledge Fountain, 2018)
Throughout history, coastal cities have been influential cities and attracted large population due to their rich resources, trade opportunities as well as eco-social and cultural transfer. Today, such a privilege has been put to question as coastal cities are facing high risk to be significantly damages if not swiped away as a result of Sea Level Rise (SLR) and floods resulting from the drastic climate change. As such, hundreds of millions of urban inhabitants in low and middleincome nations are at risk from direct and indirect negative impacts of climate change. Moreover, climate change when left undealt with may contribute in forcing migration, conflicts, hunger and destroy infrastructure worldwide. Sad but true, Egypt is ranked third on the list of countries most affected by climate change. The effects will include temperature rise, change in rain patterns, rise of sea level, and increase in catastrophic weather events with all socio-economic consequences. Alexandria, the bride of the Mediterranean, is listed among the 15 of the world’s 20 coastal megacities that are at risk from SLR and coastal surges. However, such threats can be minimized through; ‘mitigation’ where the causes of climate change can be controlled and ‘adaptation’ where cities are protected from the negative impact. The objectives of this study is to uncover, examine and assess the negative impacts and threats of climate change on coastal cities and its built environment globally, in Egypt, and particularly in Alexandria; as well as the vulnerability of Alexandria’s residents and explore their level of awareness of the impacts of climate change on their city and lives; identifying the gaps in Egypt National Climate Change Strategy that triggers the sustainability of coastal city like Alexandria; explore design parameters that promote sustainable design for buildings in areas at high risk of SLR and floods; assess the perception and knowledge of architects, professionals and policy makers on issues related to climate change and buildings. In order to fulfill these objectives, an intensive literature study and hybrid methodology were undertaken. Two questionnaires where developed for Alexandria’s residents, and architects and engineers, one to one interviews with professionals, experts and governmental and NGOs representatives. The findings of this study reveal and confirm the high vulnerability of the residents in Alexandria due to the inefficient practices, weak and poor communication between the government and the residents for climate change threats. Also, the study pinpoint poor and limited knowledge for sustainable practices and designs that need to be can adapted to climatic threats like SLR and floods. Gaps in Egypt National Climate Change Strategy was identified which did not match plan for the ministries in which facing the challenges of SLR and floods for coastal cities are considered. Clear gap strategy related to the collaboration between the responsible bodies, and the barriers and seawalls, and the lack of awareness and poor sustainable design practices by the engineers and architects have all been documented. Looking forward, a recommended framework and design guideline based on mitigation and adaptation practices for buildings and city’s sustainability have to be established in lights of the findings of this work. Such recommendations need to be transformed in the soon future into an action plan nationwide.